Simulasi Monte Carlo pada Pola Tidur Shift Worker untuk Estimasi Risiko Penyakit - Sabrina Vidya Siswantoro; Didi Suhaedi; Erwin Harahap (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Shift work can disrupt the body’s circadian rhythm and is associated with changes in sleep duration and an increased risk of chronic diseases. This study aims to model the distribution of sleep duration among day-shift and night-shift workers using Monte Carlo Simulation and to estimate the Population Relative Risk (RRpop) for Coronary Heart Disease and Type 2 Diabetes Mellitus. A total of 10,000 simulation iterations were performed for each shift using sleep duration parameters adopted from previous studies, namely = 7,53 hours (= 1,60) for day shift and = 5,74 hours (= 1,30) for night shift. Relative risk values for each sleep duration category were derived from meta-analysis studies and applied to the simulation results. Among night-shift workers, the majority exhibited short sleep duration, contributing to a higher risk of Coronary Heart Disease (RRpop= 1,1602) compared to day-shift (RRpop= 1,1096). Conversely, day-shift workers generally demonstrated adequate sleep duration but showed an increased proportion of long sleep duration, which was associated with a higher risk of Type 2 Diabetes Mellitus (RRpop= 1,1706) compared to night-shift (RRpop= 1,1390). Overall, health risks among night-shift workers are primarily driven by sleep compression, whereas risks among day-shift workers are more influenced by excessive sleep tendencies. Abstrak. Sistem kerja shift dapat mengganggu ritme sirkadian tubuh dan berhubungan dengan perubahan durasi tidur serta peningkatan risiko penyakit kronis. Penelitian ini bertujuan untuk memodelkan distribusi durasi tidur pada pekerja shift siang dan malam menggunakan Simulasi Monte Carlo, serta mengestimasi Risiko Relatif Populasi (RRpop) terhadap Penyakit Jantung Koroner dan Diabetes Melitus Tipe 2. Simulasi dilakukan sebanyak 10.000 iterasi untuk masing-masing shift dengan parameter durasi tidur yang diadopsi dari studi sebelumnya, yaitu = 7,53 jam ( = 1,60) untuk shift siang dan = 5,74 jam ( = 1,30) untuk shift malam. Nilai risiko relatif per kategori durasi tidur diadopsi dari studi meta-analisis dan diaplikasikan pada hasil simulasi. Pada pekerja shift malam mayoritas individu memiliki durasi tidur yang tergolong pendek, yang berkontribusi terhadap peningkatan risiko Penyakit Jantung Koroner (RRpop = 1,1602) dibandingkan shift siang (RRpop = 1,1096). Sebaliknya, pada kelompok shift siang mayoritas individu memiliki durasi tidur cukup, namun terdapat peningkatan pada durasi tidur berlebih, yang berdampak pada risiko Diabetes Melitus Tipe 2 yang lebih tinggi (RRpop = 1,1706) dibandingkan shift malam (RRpop = 1,1390). Dengan demikian, risiko kesehatan pada pekerja shift malam didominasi oleh kompresi waktu tidur, sementara pada pekerja shift siang risiko lebih dipengaruhi oleh kecenderungan tidur berlebih.